STUDY CATCH DREDGE NET TYPE WITH MOUTH AND GAP (SEPARATOR) DIFFERENT - Wulandari, Diah; Syofyan, Irwandy; ', Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted in December 2014 which was held at the Laboratory of Materials Capture Device and experimental ponds Faculty of Fisheries and Marine Sciences, University of Riau. This study aims to determine the variation in diameter gravel caught as well as to determine the degree of selectivity of the catch using dredge net with mouth and slit (separator) different. The method used in this study is an experimental method of fishing is catching shellfish test, using four types of scrapers with the same two mouths, two different gap. The results of this study indicate that a more selective dredge net is the type of fingers (scratch) with a gap width of 2.5 cm and rake-type lip mussels (plate) with a slit width of 2.5 cm compared with clam rake type of fingers and lip-type (plate) with a slit width of 3.5 cm, because the type of clam rake fingers with a slit width of 2.5 cm and a clam rake lip type (plate) with a slit width of 2.5 cm has the smallest range value and the value of the variance smallest.Keywords : Dredge net, selectivity, separator, plate